Product distribution in hydrogenation of styrene oxide over Pd/chitosan catalyst - Viswanadhan, Maya; Potdar, Aparna; Divakaran, Anumon V.; Badiger, Manohar V.; Rode, Chandrashekhar (Research on Chemical Intermediates, 2016)
Palladium-decorated chitosan catalyst was synthesized by an impregnation method by varying the Pd loading in the range of 1-6 %, and was evaluated for the regioselective hydrogenation of styrene oxide. In order to correlate the chemical and textural properties with the catalytic activity, all the prepared catalysts were characterized by techniques such as Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, transmission electron spectroscopy, thermo-gravimetric analysis, temperature-programmed desorption of NH3, and CO2 and N-2 physisorption. The synthesized catalysts were utilized for the efficient and regioselective ring opening of styrene oxide by hydrogenation under different conditions. The complete conversion of styrene oxide with 65 % selectivity for 2-phenyl ethanol and 33 % for 1-phenyl ethanol were obtained using 4 % Pd/CS catalyst at 70 degrees C temperature and 3 MPa pressure. The mechanism for the regio selective ring opening of styrene oxide to 1- and 2-phenyl ethanol was also proposed on the basis of properties of the catalyst support, catalytic activity and selectivity. These results indicated that the catalytic activity and selectivity of the catalysts were affected by the nature of support. Further, the basic properties of the support play an important role in the selectivity of the styrene oxide hydrogenation reaction.

Calcination temperature impacting the structure and activity of CuAl catalyst in aqueous glycerol hydrogenolysis to 1,2-propanediol - Mane, Rasika; Potdar, Aparna; Jeon, Yukwon; Rode, Chandrashekhar (Topics in Catalysis, 2024)
This study investigated the impact of calcination temperature on the structural properties of CuAl catalyst which was found to be a robust nano-structured catalyst calcined directly without ramping at 400 °C and performed exceedingly well for aqueous phase hydrogenolysis of glycerol. Various samples of CuAl catalysts were prepared by co-precipitation at Cu: Al molar ratio 1:1 and were calcined at different temperatures (300–1000 °C). The obtained catalysts were reduced at 200 °C before their activity testing for glycerol hydrogenolysis reaction. To correlate the structure-activity, the catalysts were thoroughly characterized by XRD, XPS, BET, TEM, H2-TPR, NH3-TPD, and pyridine FTIR. It was observed that with an increase in calcination temperature from 300 to 700 °C, the glycerol conversion also increased from 47 to 55% with 93% selectivity to 1,2-PDO. The better performance of these catalysts was mainly related to the predominant presence of Brønsted acid sites, an appropriate ratio of the Cu0 to CuAl2O4 + CuO (0.33) and CuAl2O4 to CuO phases (0.35), the existence of Cu2O phase and the smaller Cu0 particle size. It was shown that altering the ramping rate for the calcination temperature of 400 °C impacted the catalytic activity. The CuAl-400 (DC) (direct calcined) catalyst exhibited a maximum glycerol conversion of 60%.